Evaporative water loss and oxygen uptake in two casque-headed tree frogs, Aparasphenodon brunoi and Corythomantis greeningi (Anura, Hylidae) - deAndrade, D. V.; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 1997)
Evaporative water loss (EWL) and oxygen uptake ((V) over dot o(2)) was measured in two species of tree frogs with cranial co-ossification, Aparasphenodon brunoi and Corythomantis greeningi. Both species use their head to seal the entrance of bromeliads, tree holes or rocky crevices used as shelters. EWL was significantly reduced in sheltered individuals of both species as compared with those exposed nude to desiccation. EWL per unit area through the head surface was significantly lower than the body skin for A. brunoi but not for C., greeningi. EWL per unit surface area through C. greeningi body skin was about 50% that of A. brunoi, indicating a less permeable skin in the former species. The relationship between cranial coossification and EWL is discussed. ((V) over dot o(2)) in A. brunoi was comparable with other anurans of similar size, whereas in C. greeningi, it was lower than predicted from body mass. Moreover, ((V) over dot o(2)), in C. greeningi showed less sensitivity to temperature increase than in A. brunoi. C. greeningi occurs in a drier environment than A. brunoi, and this appears to be reflected in their EWL and ((V) over dot o(2)) characteristics. (C) 1997 Elsevier B.V.
Keywords: anura; Aparasphenodon; Corythomantis; cranial co-ossification; evaporative water loss; Hylidae; oxygen consumption; phragmosis